Hospital Wastewater-Important Source of Multidrug Resistant Coliform Bacteria with ESBL-Production - Lépesová, Kristína; Olejníková, Petra; Mackuľak, Tomáš; Cverenkárová, Klára; Krahulcová, Monika; Bírošová, Lucia (International journal of environmental research and public health, 2020)
This work compares the prevalence of antibiotic resistant coliform bacteria in hospital wastewater effluents in Slovak (SR) and Czech Republic (ČR). It also describes selected antibiotic resistant isolates in view of resistance mechanism and virulence factor. The highest number of multidrug resistant bacteria was detected in samples from the hospital in Valašské Meziříčí (ČR). More than half of resistant isolates showed multidrug resistance phenotype as well as strong ability to form biofilm. In 42% of isolates efflux pump overproduction was detected together with tetA and tetE genes. The production of extended-spectrum β-lactamases in coliform isolates was encoded mainly by blaTEM, blaCTX-M-2 and blaCTX-M-8/25 genes. About 62% of resistants contained a combination of two or more extended spectrum beta-lactamases (ESBL) genes. Our results strengthen the fact that hospital effluents are a source of multidrug resistant bacteria which can spread their resistance genes to other bacteria in wastewater treatment plants (WWTPs). Accordingly, hospital wastewater should be better treated before it enters urban sewerage.
Keywords: Microbial Sensitivity Tests; mnohočetná bakteriální léková rezistence; antibiotic resistance; mikrobiální testy citlivosti; hospital wastewaters; ESBL; antibakteriální látky; efflux pumps; Drug Resistance, Multiple, Bacterial; Wastewater; beta-laktamasy; Waste Water; Hospitals; Anti-Bacterial Agents; Czech Republic; nemocnice; beta-Lactamases; odpadní voda; Česká republika; biofilm